Cataract surgery considerations in patients with prior history of keratoconus and ectasia. Issue 1 (19th January 2023) - Moshirfar, Majid; Ziari, Melody; Ronquillo, Yasmyne C.
Abstract : Purpose of review: Preoperative workup for cataract surgery in patients with keratoconus poses certain challenges, particularly in patients with moderate-to-severe disease. This review aims to outline the appropriate preoperative, intraoperative, and postoperative considerations and provides an algorithm to help guide the workup prior to surgery. Recent findings: A new system for keratoconus progression and staging has been proposed and additional studies comparing intraocular lens (IOL) formulas calculations and biometry devices have been conducted. Summary: Patients with severe keratoconus have unpredictable results and have an increased risk of a hyperopic refraction postoperatively. Although studies have compared IOL calculation formulas, there is no consensus on management. Clinical considerations and an approach to the workup are presented; however, additional studies are required to determine the most appropriate management of cataracts in severe keratoconus.